Bank Credit Allocation in Latin America and the Caribbean - Gutierrez, Eva; Karmali, Nadeem; Sourrouille, Diego (World Bank, Washington, DC, 2018)
Despite their importance, data on the structure of bank credit by maturity are scarce. For Latin America and the Caribbean, data are particularly difficult to obtain, as few banks report loan maturity data in commercial data sets such as Bankscope. With support from the Association of Supervisors of Banks of the Americas, this study assembled a novel data set on the structure of bank credit allocation in Latin America and the Caribbean covering 21 countries during 2004-14. This paper uses Bankscope and International Financial Statistics data to extended the coverage to more than 100 countries, creating the largest data set so far on credit by maturity. Benchmarking credit structure in Latin America and the Caribbean, the paper finds that the region is financially underdeveloped, because the ratio of short-term credit to gross domestic product is lower than in peers; long-term credit is at par; and consumer and commercial loans are lower. The paper also explores patterns of credit growth through nonparametric regressions. The results indicate that short-term credit grows faster than long-term credit as income grows in low-income countries, but the situation reverses when countries reach high- or middle-income status. Reflecting this trend, the share of mortgage loans rises with income.